Computational Contact Problems: Investigations on the Robustness of Generalized Newton Method, Fixed-Point method and Partial Newton Method. Issue 4 (4th July 2018) - Kudawoo, A.D.; Abbas, M.; De-Soza, T.; Lebon, F.; Rosu, I.
Abstract: Dealing with frictional contact simulations, one can use generalized Newton method or Fixed-point method. In this article, we present partial Newton method which combines advantages from both algorithms. The solution techniques presented are based on an equivalent writing of the augmented Lagrangian formulation. Level-set functions are introduced to describe the status of the point. We consider various numerical examples especially a large scale industrial in order to compare the algorithms implemented.